Students' Perceptions of the Learning Environment and Attitudes in Game-Based Mathematics Classrooms - Afari, Ernest; Aldridge, Jill; Fraser, Barry; Khine, M.S. (Springer, 2013)
We investigated whether the introduction of games into college-level mathematics classes in the United Arab Emirates (UAE) was effective in terms of improving students’ perceptions of the learning environment and their attitudes towards of mathematics. A pre–post design involved the administration of English and Arabic versions of two surveys (one to assess students’ perceptions of the learning environment and the other to assess their attitudes) after modification to ensure their relevance for college-level mathematics students in the UAE. For a sample of 33 classes (352 students), eight of which (90 students) were exposed to mathematics games, students involved in mathematics games perceived statistically significantly more teacher support, involvement, personal relevance, enjoyment of mathematics lessons and academic efficacy.